Modeling the effect of deforestation caused by human population pressure on wildlife species - Lata, Kusum; Misra, Arvind Kumar Kumar; Shukla, Jang Bahadur Bahadur (Nonlinear Analysis: Modelling and Control, 2018)
The increase in human population has posed several problems for the ecosystem. One of these problems is the decrease in forestry resources, which leads to decline in forest area and thus threaten the survival of wildlife species as the intraspecific competition among the wildlife species increases. Moreover, these wildlife species can also be apprehended easily by poachers and smugglers. This affects the biodiversity across the globe. In this paper, we have proposed and analyzed a nonlinear mathematical model to see the effect of deforestation caused by population and its pressure on wildlife species. The analysis of proposed model reveals that, as the parameters in respect to the increase in population pressure increase, wildlife species decrease. To support analytical findings, we have done numerical simulation.
Keywords: mathematical model; forestry resources; wildlife species; human population; stability